Cultura Infantil and The Black Heralds (1918): the Pedagogical-Poetic Itinerary of César Vallejo - Carhuaricra Anco, Miguel Ángel (2020)
Between 1913 and 1917, César Vallejo published ten pedagogical poems in the school journal Cultura Infantil, which compared to The Blacks Heralds, reveal how was the transition from a pedagogical conscience to a poetic consciousness in the Santiago de Chuco’s poet. In this sense, from the principles of textual genetics and the horizon of comparativism, this research contrasts «Oscura», «Armada juvenil» and «A mi hermano muerto…», respectively, with «Los arrieros», «Terceto autóctono» and «A mi hermano Miguel». The hypothesis of this study is that the contrast among Cultura Infantil poems and The Black Heralds shows the thematological, morphological and generic evolution of Vallejo’s poetic. For this purpose, I will use the definition of an antetext established by Jean Bellemin-Noël; then clarified the concepts of thematology, morphology and genology, according to Claudio Guillén comparative perspective; finally, I will study the ideas of reception, imprint and interference, based on literary intertextuality. At the end, I analyze comparatively all the poems and reflect about the pedagogical-poetic itinerary covered by César Vallejo.